2021
DOI: 10.2166/ws.2021.206
|View full text |Cite
|
Sign up to set email alerts
|

New solar still with energy storage: application to the desalination of groundwater in the Bou-Ismail region

Abstract: This study aims to develop efficient desalination equipment that increases the distilled water production rate and enhances heat transfer in the evaporator. It focuses on the impact of equipment geometry and energy storage during the daytime and nocturnal period. Besides, the effects of the energy storage system which is placed in two specific areas on the yield of the distillation process with and without energy storage have been studied. The heat exchanger system provides the energy to the water to be treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In the RO system, seawater is pressurized and passed via a specific membrane module that allows the permeation of water while eliminating all existent solutes (Tigrine et al 2021). In general, RO desalination consists of four main parts, namely pretreatment, a high-pressure pump, membrane modules, and post-treatment (Tigrine et al 2016).…”
Section: Operation Mode Of Reverse Osmosis Filtrationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the RO system, seawater is pressurized and passed via a specific membrane module that allows the permeation of water while eliminating all existent solutes (Tigrine et al 2021). In general, RO desalination consists of four main parts, namely pretreatment, a high-pressure pump, membrane modules, and post-treatment (Tigrine et al 2016).…”
Section: Operation Mode Of Reverse Osmosis Filtrationmentioning
confidence: 99%
“…According to Figure 5, the ambient temperature ranges between 24.5 and 33.9 °C, it increases as the solar radiation increases, which reaches its maximum of 850 w/m² between 12:00 h and 14:00 h PM for the study day (July 21st, 2019). The solar system reflects 11% of solar radiation considered the most influencing parameter of the functioning of the system as mentioned by several studies (Diaf et al 2016;Mohsenzadeh et al 2021;Tigrine et al 2021). During the offshine hours from 00:00 AM to 7:00 AM and from 21:00 PM to 00:00 AM, the solar irradiation, as well as the ambient temperature, is zero.…”
Section: Salt Recovery By Solar Distillationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the productivity of the solar still with sand troughs was enhanced by 71.4% compared to the CSS. Tigrine et al (2021) studied the performance of the solar still with energy storage and electric heater. It was observed that the solar-modified still had a better yield with 50% enhancement compared to the CSS.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…A recent study has been done to improve the heat transfer inside evaporator which allow increasing the yield of distilled water. It has been found that using energy storage enhance considerably the average daily of distilled output water (Tigrine et al 2021).…”
Section: Introductionmentioning
confidence: 99%